Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538910
|View full text |Cite
|
Sign up to set email alerts
|

Neo-piagetian theory as a guide to curriculum analysis

Abstract: The development of a coherent curriculum, encapsulating appropriate topics, learning materials and assessment, is crucial for a successful educational experience. However, designing such a curriculum is a complicated task, with challenges in tracing the development of concepts across multiple courses and ensuring that assessment is at an appropriate level at specific points in the curricula.In this paper, we introduce a curriculum mapping framework based on Neo-Piagetian theory that assists lecturers in tracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Gluga et al developed a web-based system called PROGOSS that maps curricula learning goals and mastery levels to individual assessment tasks across entire degree programs [6]. Szabo et al also developed curriculum analysis framework which supports the identification of prerequisite concepts [20]. Mendez et al reported that they applied several learning analytic techniques to a curriculum [11], where the longstanding grade data of students in their institution is used for the curriculum analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Gluga et al developed a web-based system called PROGOSS that maps curricula learning goals and mastery levels to individual assessment tasks across entire degree programs [6]. Szabo et al also developed curriculum analysis framework which supports the identification of prerequisite concepts [20]. Mendez et al reported that they applied several learning analytic techniques to a curriculum [11], where the longstanding grade data of students in their institution is used for the curriculum analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Curriculum development focuses on the creation of these design specifications and constraints. It is further defined as the design, development, and implementation of guides for learning 8,17 such as topics, learning objectives, content knowledge, learning activities, and formal assessment 18 . Pratt defines the curriculum as "an organized set of formal educational and/or training intentions" which describes the curriculum as represented by the intentions of the curriculum designer 19 .…”
Section: Curriculum: Design and Mappingmentioning
confidence: 99%
“…A check could then be placed in each cell where the course contains that goal 8 . Two examples are: associating teaching and assessment methods aimed at identifying required "prerequisite concepts" and "assessment leaps" 18 ; and comparing students' and instructors' perceptions of the curriculum 9 . By comparing the perceptions of multiple parties, such as both students and instructors, curriculum designers can then make better informed decisions and create curricula that is a more accurate portrayal of how students move through the curriculum.…”
Section: Curriculum: Design and Mappingmentioning
confidence: 99%